2015
DOI: 10.1785/0120140085
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Analysis on Seismic Site Response of Fuzhou Basin, China

Abstract: Based on the parallel computing cluster platform of the ABAQUS software, a large-scale 2D finite-element refined nonlinear modeling approach was used to study seismic site effects in the Fuzhou basin, such as peak ground acceleration (PGA), spectral acceleration, duration, and acceleration transfer functions. A 1D equivalent linear wave propagation analysis was conducted also, with Proshake for supplementation and calibration. The simulation results demonstrated the following. (1) PGA amplification factors exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Only a portion of the site most influenced by ground motion is mapped onto the computational domain, with the remainder captured by an artificial boundary condition, 29,32,33,55 allowing the scattering waves to propagate through the cutoff boundaries toward the far‐field sites without reflection. The viscous‐spring artificial boundary of Liu and his colleagues, 32, 33 by transforming the bedrock input motion into the equivalent nodal loads derived by distributing the spring and dashpot system on the artificial boundary, has been proven to be effective from the results of 2D and 3D nonlinear seismic response analyses 5,34 . In the artificial boundary of Liu and his colleagues, 32, 33 uniform stress distribution in the half‐interval around the artificial boundary node is assumed (see Figure 4).…”
Section: Numerical Schemementioning
confidence: 99%
“…Only a portion of the site most influenced by ground motion is mapped onto the computational domain, with the remainder captured by an artificial boundary condition, 29,32,33,55 allowing the scattering waves to propagate through the cutoff boundaries toward the far‐field sites without reflection. The viscous‐spring artificial boundary of Liu and his colleagues, 32, 33 by transforming the bedrock input motion into the equivalent nodal loads derived by distributing the spring and dashpot system on the artificial boundary, has been proven to be effective from the results of 2D and 3D nonlinear seismic response analyses 5,34 . In the artificial boundary of Liu and his colleagues, 32, 33 uniform stress distribution in the half‐interval around the artificial boundary node is assumed (see Figure 4).…”
Section: Numerical Schemementioning
confidence: 99%
“…Where ∆D5-95,surf and ∆D5-95,bedr are the durations of surface and bedrock ground motions between the 5% and 95% Arias intensity, respectively. The ground motion duration is not only related to the characteristics of bedrock motion [16], but also closely related to seismic site response analysis methods. And these correlations are enhanced with the increase of bedrock motion intensity.…”
Section: Duration Of Ground Motionmentioning
confidence: 99%
“…Here we take these initial efforts a step further, by considering a realistic basin structure and geotechnical soil properties, obtained by a recent geotechnical survey (SAFER, Gilder et al 2020), together with a 2D nonlinear modelling approach that couples 2D basin effects and multi-dimensional soil plasticity (Oral et al 2019). Previous work showed that the amplification of ground motion due to basin effects can be severely damped by soil nonlinearity (Marsh et al 1995;Psarropoulos et al 2007;Roten et al 2014;Esmaeilzadeh et al 2019), yet a 1D wave propagation modelling approach underestimates the ground motion even when soil nonlinearity is triggered (Ragozzino 2014;Chen et al 2015;Oral et al 2019). Moreover, 2D and 3D wave propagation effects also enhance nonlinearity when multi-dimensional soil plasticity is considered, compared to 1D plasticity, which can affect final surface displacement (e.g., Oral et al 2017).…”
Section: Introductionmentioning
confidence: 99%